TAHAPAN MENGGUNTING UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI KELOMPOK USIA 4-6 TAHUN - Lukman Hamid (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2020)
Pshyco motor is a movement that only involves certain parts of the body that are carried out by small muscles. Therefore Pshyco motor movements do not really need energy, but require careful coordination and accuracy. Pshyco motor skills begin to develop, after starting with very simple activities such as holding a pencil, holding a spoon, and stirring. Cutting is easy, but if it does not go through the proper steps, the results of the cut will not be as expected. Scissors is a continuation of the stages of paper tearing activities in early childhood, cutting activities intended to train the child's Pshyco motorics, especially training the fingers of the child with paper media and knobs with certain stages and patterns